"It is like the king and his kingdom": mapping constellations via the model of the agonistic self methodology (MAS-M). Issue 2 (3rd April 2023) - Grbić, Sanja; Džinović, Vladimir; Vesić, Dragan
ABSTRACT: Building on the Dialogical Self Theory (DST) and the Model of Agonistic Self (MAS), this paper introduces the Model of Agonistic Self Methodology (MAS-M). This approach employs constellations as the interpretative framework for the qualitative analysis of data on the self-in-context. Constellations are defined as wider patterns of interactions between voices which follow specific and repetitive scenarios. In order to develop MAS-M, reflexive thematic analysis was performed on individual reports written after interviewing nine elementary school teachers. The data was gathered during two-stage interview process employing the Agonistic Self Interview (ASI), which was introduced into the standard MAS-M procedure. We identified six constellations, whose structure and dynamics were formally described: The King and His Kingdom constellation, Crisis Intervention, Defense of Purpose, Value Conflict, Temporary Inclusion of Sidelined Perspectives, and Reflection. We will discuss the psychological function of each constellation, and their future application as a practical, diagnostic, and research framework.